PENERAPAN PAIKEM UNTUK MENINGKATKAN MOTIVASI BELAJAR TEMA INDAHNYA KERAGAMAN DI NEGERIKU PADA SISWA KELAS IV SDN 001 SAMARINDA ULU TAHUN PEMBELAJARAN 2018/2019 - Agus Salim, Nur; Hikmah, Nurul; Nur Latifah, Tika (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
This study intended to increase the motivation to learn the beautiful theme of diversity in my country using the application of PAIKEM to fourth grade students at SDN 001 Samarinda Ulu in 2018/2019. This type of research is classroom action research conducted in II cycle, and each cycle consisted of 2 meetings. The results showed that (1) The application of PAIKEM in learning can increase the activities of teachers and students. In the first cycle scored 75 to 96, it was also proven by observing student activities, which scored 67 with a percentage of 52%. in the first cycle, increasing in the second cycle to 81 with a percentage of 93%. (2) Learning outcomes in theme 7 sub theme 3 social studies content have increased after action. The data showed the average value of the first cycle of 74.31 with a percentage of completeness that is 69%, in the second cycle to 85.51 with 90% completeness. (3) Students' learning motivation while learning in cycle I 48% increased in cycle II to 93% Based on the results of the study, the application of PAIKEM can increase learning motivation